Pengaruh penyuluhan terhadap pendapatan peternak babi di desa Kiawa dua Timur Kecamatan Kawangkoan Utara - Hutabarat, S J; Sajow, A A; Lombogia, S O. B; Warouw, Z M (ZOOTEC, 2021)
THE EXTENSION EFFECT ON THE INCOME OF PIG FARMERS IN KIAWA DUA TIMUR VILLAGE, KAWANGKOAN UTARA SUB-DISTRICT. The research was conducted in Kiawa Dua Timur village, Kawangkoan district, Minahasa district for one month from June to July 2020. This study aims to determine the effect of counseling on increasing the income of pig farmer groups in Minahasa Regency by taking the case in Kiawa Dua Timur village, Kawangkoan Utara district. This research applies survey research in the form of descriptive tabular. Descriptive analysis is used to explain general things then tabular is used to explain the relationship between variables in tabular form. The survey was conducted by interview method with a questionnaire guide. Interviews were conducted using structured interview methods and questionnaire data collection methods which were distributed to thirty respondents of farmers. The results of studyÂ  showed that extension services have a very big influence on increasing the income of the members of the pig farmers in the village of Kiawa Dua Timur. The income of farmers before counseling wasÂ  Rp. 5.833 / month. Meanwhile, the farmer's income after the counseling was Rp.880.333/ month. The pig farming business carried out by the farmer group in Kiawa Dua Timur Village, North Kawangkoan District is economically profitable and feasible to develop.